Immunity and inflammation in pulmonary arterial hypertension: From pathophysiology mechanisms to treatment perspective - Ran-ran Wang; Tian-yi Yuan; Jian-mei Wang; Yu-cai Chen; Jiu-liang Zhao; Meng-tao Li; Lian-hua Fang; Guan-hua Du (Elsevier, 2022)
Pulmonary arterial hypertension (PAH) is a severe cardiopulmonary dysfunctional disease, characterized by progressive vascular remodeling. Inflammation is an increasingly recognized feature of PAH, which is important for the initiation and maintenance of vascular remodeling. High levels of various inflammatory mediators have been documented in both PAH patients and experimental models of PAH. Similarly, multiple immune cells were found to accumulate in and around the wall of remodeled pulmonary vessels and in the vicinity of plexiform lesions, respectively. On the other hand, inflammation is also a bridge from autoimmune diseases to PAH. Autoimmune diseases always lead to chronic inflammation, characterized by the low-level persistent infiltration of immune cells, and elevated levels of several pro-inflammatory cytokines and chemokines. In addition, circulating autoantibodies are found in the peripheral blood of patients, indicating a possible role of autoimmunity in the pathogenesis of PAH. Thus, anti-inflammatory and immunotherapy might be new strategies to prevent or even reverse the process of PAH. Many anti-inflammatory agents and immunotherapies have been confirmed in animal models while some clinical trials employing immunotherapies are completed or currently underway. Here, we review pathological mechanisms associated with inflammation and immunity in the development of PAH, and discuss potential interventions for the treatment of PAH.